Safety and Efficacy of a New Posterior Chamber Phakic Intraocular Lens in Cases of High Myopia: Early Results - Subudhi P (Dove Medical Press, 2020)
Praveen Subudhi,1,2 Sweta Patro,1 Prateek Agarwal,3 Zahiruddin Khan,2 B Nageswar Rao Subudhi,1 Chandan Mekap,1 Asutosh Padhi4 1Cornea and Refractive surgery services, Ruby Eye Hospital, Berhampur, Odisha, India; 2Ophthalmology Department, Hitech Medical College, Bhubaneswar, Odisha, India; 3Cleveland Clinic, Abu Dhabi, United Arab Emirates; 4George Clinicals, Hyderabad, IndiaCorrespondence: Praveen SubudhiRuby Eye Hospital, Govinda Vihar, Sushruta Nagar, Ganjam, Berhampur, Odisha, IndiaEmail subudhipraveen@gmail.comPurpose: To demonstrate the visual outcomes of a foldable, hydroxy ethyl-methacrylate, single-piece, posterior chamber phakic intraocular lens (pIOL).Study Type: Retrospective study.Materials and Methods: Patients presenting with moderate to high myopia who underwent surgical correction with a posterior chamber phakic IOL (refractive intraocular lens, phakic intraocular lens, Appasamy Associates, Chennai, India) were retrospectively reviewed. Only patients with at least one-year follow-up were included. Manifest refraction, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), endothelial cell density (ECD), and pIOL vault were analyzed 1, 3, 6, and 12 months after surgery. Intraoperative and postoperative events were recorded in all cases.Results: The study included 30 eyes from 15 patients. The mean patient age was 25.8 ±  3 years. The spherical equivalent of manifest refraction was − 11.47 ±  4.38 D preoperatively and − 0.44 ±  0.55 D postoperatively. The preoperative CDVA was 0.17 ±  0.12 logMAR. The postoperative UDVA was 0.053 ± 0.11 logMAR (min: − 0.17 and max: 0.2) and 0.019 ± 0.091 logMAR (min: − 0.17 and max: 0.2) at the end of 1 month and 6 months, respectively. At the end of the 12-month visit, the postoperative UDVA was 0.032 ± 0.094, and the safety index was 2.42. The mean ECD was 2639 cells/mm2 (min: 2389 and max: 2993 with SD: 139.53) at the preoperative visit and 2445 cells/mm2 (min: 2050 and max: 2701) at the 12-month visit (5.8% loss, p less than 0.001). ECD loss from 6 months to 12 months was not statistically significant. No significant cataract formation, significant endothelial cell loss, glaucoma, uveitis, or any other vision-threatening complication were observed.Conclusion: Based on postoperative experience, we found that RIL phakic IOLs are safe and effective for treating high myopia at short-term follow-up.Keywords: refractive intraocular lens, RIL, myopia, phakic lens